GERAK SINKRON: PERAN GERAK DAN MUSIK BAGI HUBUNGAN INTERPERSONAL ANAK USIA DINI - Yuda Oktadus, Henry; F.A. Yaqin, Ahmad (Institut Seni Indonesia (ISI) Surakarta, 2024)
Musical activities are often said to promote positive social experiences; however, certain conditions can hinder the success of children's social interactions during these activities. For instance, overly challenging musical tasks, unresolved interpersonal conflicts, and high levels of competition in group music settings may introduce pressures that inhibit collaboration and social engagement. Therefore, it is essential to investigate the factors that are crucial for fostering successful social dynamics in children's group musical activities. This article aims to explore how movement elements can influence the social interactions within these group settings. Hove and Risen's (2009) concept of interpersonal synchronization is employed to explain how feelings of safety and enjoyment emerge during movement-based music activities. This framework aligns with Hirschi's (1969) model, which outlines the prerequisites for forming social bonds in collective activities. Qualitative data were collected at Hanacaraka Edukids Montessori School Kindergarten in Yogyakarta through semi-structured interviews with three teachers and sixteen of the thirty-two participating children. The data were then analyzed using Schreier's (2014) content analysis procedures. The findings suggest that incorporating movement into group music activities can enhance children's positive mood, which, in turn, fosters positive interactions and strengthens friendships within the group. Keywords: music and movement, early childhood, interpersonal relationship